Effect of aminoglycosides on the pathogenic characteristics of microbiology. (December 2017) - Xu, Zhenbo; Xu, Xingyong; Qi, Da; Yang, Ling; Li, Bing; Li, Lin; Li, Xiaoxi; Chen, Dingqiang
Abstract: Infections caused by pathogen remain to be one of the most important global health issues, and scientists are devoting themselves to seeking effective treatments. Aminoglycoside antibiotics are one kind of widely used antibiotics because of the good efficiency and broad antimicrobial-spectrum. However, it causes some unexpected effects on the pathogenic characteristics of microbiology during the treatment, such as drug resistance and biofilm promotion. Drug resistance is partly due to antibiotics abuse. Simultaneously, aminoglycoside is documented to make divergent effects on biofilm based on their concentrations. Here, we review the mechanism of drug resistance caused by long-term use of aminoglycoside antibiotics, the effects of antibiotic concentration on biofilm formation and the negative effects on intestinal flora to provide theoretical supports for rational use of antibiotics. Highlights: Microbiology and biofilm are major culprits for nosocomial infection and effects of antibiotics are presented. The mechanism of drug resistance and biofilm formation caused by aminoglycoside are talked in detail. The balance of gut flora is so important that much attention have been paid and advice on related topic present as well.